(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Employees are the most important element in determining the advancement of a company. To achieve company goals are required employees by the requirements within the company. The company must be able to perform tasks that have been determined before. The purpose of this research is to prove and analyze the influence of Person Organization Fit on Organizational Commitment, Person Organization Fit on Employee Performance, Career Plateau on Organizational Commitment, Career Plateau on Employee Performance, Leader-Member Exchange (LMX) to Organizational Commitment, Leader-Member Exchange (LMX) to Performance Employee and Organizational Commitment to Employee Performance. The method of this research is using a quantitative method. The population is all of the employees in BKPSDA Bangkalan regency with a sample of 61 peoples. Data collection is using the questionnaire method. Data analysis techniques are using Smart Partial Least Square (PLS) version 3.2.7. The result shows that H1 is rejected, where Person Organization Fit has no significant effect on organizational commitment, H2 is accepted where Person Organization Fit has a significant effect on employee performance, H3 is accepted where Leader-Member Exchange has a significant effect on organizational commitment, H4 is rejected where Leader-Member Exchange does not affect the performance of employees, H5 is rejected where Organizational Commitment has no significant effect on employee performance, H6 is accepted where the Career Plateau has a significant effect on Organizational Commitment H7 is accepted where the Career Plateau has a significant effect on employee performance.